2016
DOI: 10.1080/00288306.2016.1168455
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical imaging of disrupted coastal dune stratigraphy and possible mechanisms, Haast, South Westland, New Zealand

Abstract: Geophysical imaging of coastal dune stratigraphy near Haast, South Westland, provides insight into coseismic dune modification on a seismically active coastline. Ground penetrating radar (GPR) reveals two low-angle features that apparently truncate and offset dune bedding. Complex attribute analysis of the GPR profiles, and a distinct electrical resistivity response, are consistent with truncated bedding. One feature is near-coastal and separates post-seismic dunes that have been attributed to the 1717 and 182… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…These studies have shown geophysical images of faulting, supporting and/or extending observations on outcrops, boreholes, and trench data and contributed to base knowledge of seismogenic structures as well as to the seismic hazard assessment of several regions around the world. Among the pioneers, we can mention Benson (1995), Smith and Jol (1995), Busby and Merritt (1999), Cai et al (1996), andLiner andLiner (1997), and in the successive 20 years, other 2D GPR studies were achieved across several faults worldwide (Audru et al, 2001;Demanet et al, 2001;Overgaard and Jakobsen, 2001;Bano et al, 2002;Liberty et al, 2003;Reiss et al, 2003;Slater and Niemi, 2003;Malik et al, 2007;Wallace et al, 2010;Yalciner et al, 2013;Imposa et al, 2015;Anchuela et al, 2016;Nobes et al, 2016;Matos et al, 2017;Pousse-Beltran et al, 2018;Zajc et al, 2018;Zhang et al, 2019 andShaikh et al, 2020). In Italy, only a few GPR studies are currently available across normal faults (e.g., Salvi et al, 2003;Jewell and Bristow, 2006;Pauselli et al, 2010;Roberts et al, 2010;Ercoli et al, 2013aErcoli et al, , 2014Bubeck et al, 2015;Cinti et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…These studies have shown geophysical images of faulting, supporting and/or extending observations on outcrops, boreholes, and trench data and contributed to base knowledge of seismogenic structures as well as to the seismic hazard assessment of several regions around the world. Among the pioneers, we can mention Benson (1995), Smith and Jol (1995), Busby and Merritt (1999), Cai et al (1996), andLiner andLiner (1997), and in the successive 20 years, other 2D GPR studies were achieved across several faults worldwide (Audru et al, 2001;Demanet et al, 2001;Overgaard and Jakobsen, 2001;Bano et al, 2002;Liberty et al, 2003;Reiss et al, 2003;Slater and Niemi, 2003;Malik et al, 2007;Wallace et al, 2010;Yalciner et al, 2013;Imposa et al, 2015;Anchuela et al, 2016;Nobes et al, 2016;Matos et al, 2017;Pousse-Beltran et al, 2018;Zajc et al, 2018;Zhang et al, 2019 andShaikh et al, 2020). In Italy, only a few GPR studies are currently available across normal faults (e.g., Salvi et al, 2003;Jewell and Bristow, 2006;Pauselli et al, 2010;Roberts et al, 2010;Ercoli et al, 2013aErcoli et al, , 2014Bubeck et al, 2015;Cinti et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…These studies have shown geophysical images of faulting, supporting and/or extending outcrop, borehole, trench data, and contributing to base-knowledge of seismogenic structures as well as to the seismic hazard assessment of several regions around the world. Among the pioneers, we can mention Benson (1995), Smith and Jol (1995), Busby and Merritt (1999), Cai et al (1996) and Liner and Liner (1997), and on the successive twenty years, other 2D GPR studies were achieved across several faults (Audru et al 2001;Demanet et al 2001;Overgaard and Jakobsen, 2001;Bano et al 2002;Liberty et al 2003;Reiss et al 2003;Slater and Niemi, 2003;Malik et al 2007;Wallace et al 2010;Yalciner et al 2013;Imposa et al 2015;Anchuela et al 2016;Nobes et al 2016;Matos et al 2017;Pousse-Beltran et al 2018;Zajc et al 2018;Zhang et al 2019 andShaikh et al 2020). A few GPR surveys have been acquired across Italian normal faults (Salvi et al 2003;Jewell and Bristow, 2006;Pauselli et al 2010;Roberts et al 2010;Ercoli et al 2013a;Bubeck et al 2015;Cinti et al 2015).…”
Section: Methodsmentioning
confidence: 99%
“…As sediment supply in the nearshore returns to normal following the pulse from the storm input, the system returns to a gradual progradation as successive swash bars are welded to the beach face and sea levels continue to fall (Carter, 1986). Although the authors agree the most likely cause of the observed scarp is through storm action, they also acknowledge the possibility of causation by some other high-energy event such as tsunami, given the tectonic setting of the South Pacific and the number 1615 STORM RESPONSE ON A MIXED SAND GRAVEL BEACH RIDGE PLAIN of tsunami deposits preserved in the archaeological record (McFadgen and Goff, 2007;Nobes et al, 2016).…”
Section: Storm Responsementioning
confidence: 99%
“…It is expected that rapid sedimentation at the coast would follow the catastrophic failure of a large regional fault such as the Hope or Porter's Pass Faults. Failures of the Alpine Fault have been observed to create rapid dune development and progradation on the west coast of New Zealand in locations that do not experience rapid dune growth under normal conditions (Wells and Goff, 2007;Goff, 2008;Nobes et al, 2016). Rapid fluvial transfer of fine materials from the Southern Alps to the east coast through rivers such as the Waimakariri has also been proposed (McFadgen and Goff, 2007).…”
Section: Site Overviewmentioning
confidence: 99%